2020
DOI: 10.3390/healthcare8010026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Empathy in Health and Social Care Professionals

Abstract: The current article is an integrative and analytical literature review on the concept and meaning of empathy in health and social care professionals. Empathy, i.e., the ability to understand the personal experience of the patient without bonding with them, constitutes an important communication skill for a health professional, one that includes three dimensions: the emotional, cognitive, and behavioral. It has been proven that health professionals with high levels of empathy operate more efficiently as to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
230
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(266 citation statements)
references
References 61 publications
17
230
0
19
Order By: Relevance
“…An important result obtained in this study is the high level of anxiety that has been detected: 6.38 points while the mean measure in Spanish population is 5.5 points [34]. This result is in accordance with other research showing that the prevalence of anxiety in nurses is higher than in the whole population, indicating that registered staff nurses as a collective come under different kinds of pressure related with their clinical activity [27,29,31] that finally predispose to mildly alterations like anxiety [22,40,41]. These findings coincide with our second research hypothesis in which staff nurses are a collective with a high values of personal traits related with anxiety management.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…An important result obtained in this study is the high level of anxiety that has been detected: 6.38 points while the mean measure in Spanish population is 5.5 points [34]. This result is in accordance with other research showing that the prevalence of anxiety in nurses is higher than in the whole population, indicating that registered staff nurses as a collective come under different kinds of pressure related with their clinical activity [27,29,31] that finally predispose to mildly alterations like anxiety [22,40,41]. These findings coincide with our second research hypothesis in which staff nurses are a collective with a high values of personal traits related with anxiety management.…”
Section: Discussionsupporting
confidence: 90%
“…These data suggest that staff nurses are affable, cooperative and that enjoys the company of others and receptive to other points of view and opinions, characteristics that have a very specific bearing on the role of nurses over the patients' care [44]. This result is according to previous studies which have identify nurses as empathic people [16,31]. These findings coincide with our first research hypothesis in which staff nurses are a collective with a high personal traits related with empathy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Perspective-taking was the empathy capability and previous studies portrayed empathy as a feminine virtue. 31 This study showed that being empathetic can be a masculine feature. Recent studies also revealed patients' satisfaction with male nurses' being empathetic.…”
Section: Discussionmentioning
confidence: 76%